Faculties’ perception about Problem-Based Learning in remote education during pandemic COVID-19 (Research, Society and Development, 2021)
The great challenge for medical schools during the COVID-19 pandemic was to make the transition, in a short period, from face-to-face teaching of Problem Based Learning (PBL) to remote emergency teaching (ERT). This paper had the objective to report the results of the implementation of the PBL in the ERT in the medical faculty of a University Center in Fortaleza. This is a cross-sectional, descriptive and quantitative study. An electronic form in Google Docs format, sent to all teachers after completing the tutoring activities in the first academic semester of 2020, assessed their perception of the effectiveness of PBL in the ERT, the difficulties of adapting to this modality, the cognitive overload of tutorial sessions and the interfering factors in the online tutor-student interaction. The docents signed a consent form and anonymity was guaranteed.  89 tutors responded to the form, 60.7% were female, with an average age of 40.9ys and the median time of experience as a tutor was two-years. Regarding the effectiveness of PBL in the ERT, 49.4% of the tutors considered it was lower compared to classroom teaching; 70.8% had no/minimal experience with educational technologies before the pandemic; 46.1% had difficulties in adapting to the ERT modality; 69.6% evidenced the students' cognitive overload and 74.1% agreed with the need to reduce the tutoring hours. The main factors that interfered in the tutor-student interaction were interruption of the internet network, camera turned off and deficient non-verbal communication. Therefore, the use of PBL in the ERT should be carried out in a modified way, with reduced hours of synchronous activities, with better training of tutors and students in TICs, better knowledge of interactive online assessments and prophylactic measures of zoom fatigue.